The Role of Employee Engagement in Mediating Perceived Organizational Support and Employee Development on Work Motivation - Muhammad Girindra Syahdi; Hardani Widhiastuti; Rusmalia Dewi (Eduvest - Journal of Universal Studies, 2024)
This study was motivated by the problems of employees at PT. X who experienced fluctuating work motivation, lack of perceived organizational support, lack of employee engagement, especially in decision-making, but indirectly in terms of employee development that has been implemented, it has led to an increase in work motivation due to the absence of employee development programs to improve employee work motivation. This study aims to examine the relationship between perceived organizational support and employee development with work motivation through employee engagement as an intervening variable at PT. X. The method used in this study was a quantitative method with an explanatory research approach. The sampling technique used was simple random sampling. The sample in this study consisted of 164 contract employees at PT. X. The data analysis technique used was path analysis with Partial Least Square (PLS). The results showed that all hypotheses were accepted. Perceived organizational support and employee development have a positive effect on work motivation (t-statistic value > 1.96 and p-value < 0.05). Employee engagement is proven to strengthen the influence of perceived organizational support and employee development on work motivation (t-statistic value > 1.96 and p-value < 0.05). The conclusion of this study is that perceived organizational support and employee development have a positive relationship with employee work motivation through employee engagement as an intervening variable.